Tingkat Keramahan Alat Tangkap Purse Seine yang Mendarat di Pelabuhan Perikanan Samudra (PPS) Cilacap Jawa Tengah - Alya Nida Marbella Arifiana; Yusrudin Yusrudin; Sumaryam Sumaryam (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2026)
This study aims to analyze the level of environmental friendliness of purse seine fishing gear used by fishermen landing their catches at the Ocean Fishing Port (PPS) Cilacap, Central Java. Environmentally friendly fishing gear is an essential component in achieving sustainable fisheries management, as it can minimize negative impacts on marine ecosystems and ensure the sustainability of fish resources. Purse seine is known as a highly efficient fishing gear for catching pelagic fish; however, its potential environmental impacts, such as bycatch, habitat degradation, and overexploitation, require further assessment. The research methods included field observations, interviews with fishermen, and secondary data analysis from relevant institutions, using indicators based on the FAO Code of Conduct for Responsible Fisheries (CCRF) to evaluate environmental friendliness aspects. The results of this study are expected to illustrate the extent to which the use of purse seine at PPS Cilacap meets the criteria of environmentally friendly fishing gear, as well as to provide recommendations for more sustainable capture fisheries management. This research is expected to serve as a reference for the government and stakeholders in formulating policies on the use of effective, equitable, and environmentally friendly fishing gear.